Black cumin (Nigella sativa L.) Yield Affected by Irrigation and Plant Growth Promoting Bacteria - Mohammad Reza Haj Seyed Hadi; Mohammad Taghi Darzi; Gholamhossein Riazi (Journal of Medicinal Plants and By-products, 2016)
This study was conducted to assess the effects of irrigation and plant growth promoting bactera on seed yield and qualitative characteristics of Black cumin (Nigella sativa L.) at the Experimental Station of the Research Institute of Forest and Rangeland, Damavan region, Iran. A split-plot experimental design, based on Randomized Complete Block Design (RCBD) with three replications, was used. Irrigation treatment at three levels (normal irrigation (control), irrigation terminated at the start of budding and irrigation terminated at the start of ﬂowering) allocated in main plots and plant growth promoting bacteria treatment at four levels (non-inoculated, seed inoculated, spraying on the plant base at stem elongation stage and seed inoculated + spraying on the plant base at stem elongation stage) were arranged in sub-plots. Measured traits were consisted of harvest index, seed yield, essential oil, carvone and thymoquinon content. Results showed that the highest harvest index (28.20%) and seed yield (722.85 kg/ha) were obtained by normal irrigation. But, irrigation terminated at the start of budding caused the maximum essential oil (0.45%), carvone (0.018 mM) and thymoquinon content (0.021mM). Applying spraying plant growth promoting bacteria on the plant base at stem elongation stage and seed inoculated + spraying on the plant base at stem elongation stage caused highest seed yield (611.59 kg/ha) and thymoquinon content (0.019 mM). Maximum essential oil (0.45%) and carvone content (0.020 mM) was obtained by seed inoculation with plant growth promoting bacteria.